Draft Annual Plan 1989-90 Volume II Statistical Statement Union Territory of Chandigarh - Planning Commission (Planning Commission, 1989)
In order to ensure regular cleanliness, the responsibility for providing sanitary condition in villages is proposed to be handed over to the health deptt. M.O.H . Previously only negligible staff were provided for sanitation purpose. At present, there is about 40,000 rural population, if we hive to improve the sanitation of Chandigarh we have to make up the sanitation of the surrounding areas. Only four villages namely Burail, Attawa, Badheri and Buterla fall in the master plan of Chandigarh but in the interest of tie proper sanitation of the city beautiful we will have to take up the entire rural area under the sanitation programme and to provide them the following sanitation facilities.
Union Territory of Chandigarh